Metode Kromatografi Cair Kinerja Tinggi Menggunakan Kolom Oktil Silika Fully Endcapped Residual Silanol pada Pemisahan Kotinin dan 3-Hidroksikotinin dalam Sampel Urin - CHRISTINE PATRAMURTI; SUDIBYO MARTONO; SUGIYANTO SUGIYANTO; ARIEF NURROCHMAD (Fakultas Farmasi Universitas Pancasila, 2014)
Cotinine (COT) and 3-hydroxycotinine (3-HCOT) are nicotine metabolite excreted in urine. Mediated by the enzyme cytochrome P450 2A6 (CYP 2A6), nicotine will be metabolized to COT and 3-HCOT. The activity of CYP 2A6 can be predicted from the ratio 3-HCOT to the COT, therefore the ratio of 3-HCOT and COT can be used as phenotyping and polymorphism studies of the enzyme. In this study, isolation COT and 3-HCOT of urine samples was carried out by liquid-liquid back extraction. Simultaneous analysis of COT and 3-HCOT using High Performance liquid Chromatography (HPLC) was performed by a reversed-phase octyl silica column (C8; Shimadzu 250 × 4.6 mm, 5 μm) fully endcapped residual silanol. The internal standard solution (SI) was acetanilide. The mobile phase which separate COT, 3-HCOT and SI was methanol : ammonium acetate 5 mM (50:50) at a flow rate 0.8 mL/min. Retention time (tR) of the three compounds was less than 10 minutes, with peak tailing factor (tf) was less than 2. The resolution (Rs) 3-HCOT to COT was 2.67, while the Rs COT to SI was 8.836.